Sociology of Twitter/X: Trends, Challenges, and Future Research Directions - Murthy, Dhiraj (Annual review of sociology, 2024)
This article provides a sociology of Twitter (now known as X) and charts the development of the study of the platform and its data in sociological venues through an analysis of 1,644 articles published since 2009. This review helps readers understand developments in the field and provides a road map for advancing future Twitter-related sociological research. The works cited in this review advance sociological research on a variety of subfields, including but not limited to race, social movements, segregation, politics, violence, and stratification. After a brief introduction of definitions as well as methodological approaches used to study the platform (computational, qualitative, and mixed), I explore how Twitter has been used in sociological research. Furthermore, using social movements and activism as a case study, I highlight what the platform's usage and communication reveal about the social world. I conclude with a road map for advancing Twitter-related sociological research in the current atmosphere in which Twitter has been renamed X. Ultimately, a sociology of Twitter does not need to be tethered to the platform per se, as it also provides a framework for understanding new platforms if they become home for what people previously posted to Twitter/X.